Functional Antibody Responses to Severe Acute Respiratory Syndrome Coronavirus 2 Variants in Children With Coronavirus Disease 2019, Multisystem Inflammatory Syndrome in Children, and After Two Doses of BNT162b2 Vaccination . (26th May 2022) - Rostad, Christina A; Chen, Xuemin; Sun, He ying; Hussaini, Laila; Lu, Austin; Perez, Maria A; Hsiao, Hui Mien; Anderson, Larry J; Anderson, Evan J
Abstract: Background: Although neutralizing antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) correlate with protection against coronavirus disease 2019 (COVID-19), little is known about the neutralizing and antibody-dependent cell-mediated cytotoxicity (ADCC) responses to COVID-19, multisystem inflammatory syndrome in children (MIS-C), and COVID-19 vaccination in children. Methods: We enrolled children 0–21 years of age with a history of COVID-19 (n = 13), MIS-C (n = 13), or 2 doses of BNT162b2 vaccination (n = 14) into a phlebotomy protocol. We measured pseudovirus neutralizing and functional ADCC antibodies to SARS-CoV-2 variants, including Omicron (B.1.1.529). Results: The primary BNT162b2 vaccination series elicited higher neutralizing and ADCC responses with greater breadth to SARS-CoV-2 variants than COVID-19 or MIS-C, although these were diminished against Omicron. Conclusions: Serologic responses were significantly reduced against variants, particularly Omicron. Abstract : Binding, neutralizing, and antibody-dependent cell-mediated cytotoxicity (ADCC) responses against SARS-CoV-2 variants including Omicron (B.1.1.529) were assessed in children with MIS-C, convalescing from COVID-19, and after BNT162b2 vaccination. Vaccination elicited greater and broader responses against variants than COVID-19 or MIS-C.